2022
DOI: 10.1055/a-1707-1437
|View full text |Cite
|
Sign up to set email alerts
|

Robotisch assistierte totale Gastrektomie mit D2-Lymphadenektomie und intrakorporaler Rekonstruktion

Abstract: ZusammenfassungDie robotisch assistierte totale Gastrektomie beim Magenkarzinom ist eine anspruchsvolle Operation, die in Asien, aber zunehmend auch in Europa in spezialisierten Zentren durchgeführt wird. Die minimalinvasive Resektion, aber vor allem die Lymphadenektomie und minimalinvasive intrakorporale Ösophagojejunostomie sind technisch anspruchsvolle operative Schritte, deren Technik international in verschiedenen Variationen durchgeführt wird. In dem vorgestellten Video zeigen wir die robotisch assistier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The former is completed under laparoscopy ( in vivo ), while the latter requires an auxiliary incision in vitro. However, for obese patients, total gastrectomy and esophagojejunal anastomosis in vitro with the aid of an abdominal incision are very difficult to perform, and the surgical incision must be prolonged, which ultimately extends the operation time and even increases the surgical risk and postoperative pain of patients[ 30 - 33 ]. The results of this meta-analysis showed that the average BMI of the TLTG group was significantly greater than that of the LATG group, and the length of surgical incision was significantly shorter than that of the LATG group; however, there were no statistically significant differences in the total operation time, anastomotic time, or postoperative pain score between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The former is completed under laparoscopy ( in vivo ), while the latter requires an auxiliary incision in vitro. However, for obese patients, total gastrectomy and esophagojejunal anastomosis in vitro with the aid of an abdominal incision are very difficult to perform, and the surgical incision must be prolonged, which ultimately extends the operation time and even increases the surgical risk and postoperative pain of patients[ 30 - 33 ]. The results of this meta-analysis showed that the average BMI of the TLTG group was significantly greater than that of the LATG group, and the length of surgical incision was significantly shorter than that of the LATG group; however, there were no statistically significant differences in the total operation time, anastomotic time, or postoperative pain score between the two groups.…”
Section: Discussionmentioning
confidence: 99%